A Joint Technology Combining the Advantages of Capillary Microsampling with Mass Spectrometry Applied to the Trans-Resveratrol Pharmacokinetic Study in Mice. (17th January 2022) - Xu, Ying; Zhang, Song-xia; Guo, Jing; Chen, Li-jie; Liou, Yu-ligh; Rao, Tai; Peng, Jing-bo; Guo, Ying; Huang, Wei-hua; Tan, Zhi-rong; Ou-yang, Dong-sheng; Zhou, Hong-hao; et al.
Abstract : Mice are the most frequently used animals in pharmacokinetic studies; however, collecting series of blood samples from mice is difficult because of their small sizes and tiny vessels. In addition, due to the small sample size, it is problematic to perform high required quantification. Thus, present work aims to find an effective strategy for overcoming these challenges using trans-resveratrol as a tool drug. Based on the idea of a joint technology, the capillary microsampling (CMS) was chosen for blood sample collection from mice after delivery of trans-resveratrol (150 mg/kg) by gavage, and a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was developed for the determination of trans-resveratrol and its main metabolites. All the mouse blood samples were exactly collected by CMS without obvious deviation. This provided credible samples for subsequent quantitative analysis. The HPLC-MS/MS method was found to be sensitive, accurate, and repeatable, and the pharmacokinetic parameters for all analytes were comparable with those reported in previous studies. However, the present joint technology offers the advantages of less animal damage, easy for sample preparation, and improved reliability. It has overcome some of the major limitations revealed in previous pharmacokinetic studies in mice and therefore provides a more effective option for future studies.